2022
DOI: 10.1186/s12879-022-07582-1
|View full text |Cite
|
Sign up to set email alerts
|

The tryptophan catabolite or kynurenine pathway in COVID-19 and critical COVID-19: a systematic review and meta-analysis

Abstract: Background Coronavirus disease 2019 (COVID-19) is accompanied by activated immune-inflammatory pathways and oxidative stress, which both induce indoleamine-2,3-dioxygenase (IDO), a key enzyme of the tryptophan (TRP) catabolite (TRYCAT) pathway. The aim of this study was to systematically review and meta-analyze the status of the TRYCAT pathway, including the levels of TRP and kynurenine (KYN) and the activity of IDO, as measured by the ratio of KYN/TRP. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 99 publications
3
37
0
Order By: Relevance
“…Slightly different results have been observed by Almulla et al (2022). Similar to other researchers, they noticed an increase in the KYN/TRP ratio but it was not accompanied by a significant increase in KYNA [ 178 ]. All the above-described changes are indicative of activation of the kynurenine pathway among COVID-19 patients and appear to shift towards Th1 mediated activation of microglial IDO.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Slightly different results have been observed by Almulla et al (2022). Similar to other researchers, they noticed an increase in the KYN/TRP ratio but it was not accompanied by a significant increase in KYNA [ 178 ]. All the above-described changes are indicative of activation of the kynurenine pathway among COVID-19 patients and appear to shift towards Th1 mediated activation of microglial IDO.…”
Section: Resultssupporting
confidence: 86%
“…These disorders are so specific that the level of TRP below 105 μM and KYN above 5.3 μM has 95% of AUC in the differentiating of the COVID (−) and COVID (+) groups [ 176 ]. Many studies have also shown increase in the KYN/TRP ratio and its positive correlation with the severity of COVID-19 [ 177 , 178 , 179 , 180 ]. Other metabolites of kynurenic acid which are elevated in SARS-CoV-2-infected patients include 3-HK, PA, AA and 3-HAA [ 177 , 179 , 180 ].…”
Section: Resultsmentioning
confidence: 99%
“…Men have more severe acute respiratory syndrome and critical COVID-19 during acute COVID-19 infection, whereas women have more sickness symptoms and fatigue [ 20 ]. Such differences may be explained by the effects of different neuro-immune pathways, with males having a more activated NLRP3 inflammasome, which leads to severe acute respiratory syndrome [ 20 ], and females having increased cytokine-induced activation of indoleamine-2,3-dioxygenase, which is associated with acute COVID-19, depression, anxiety, and chronic fatigue [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, our negative results concerning TRYCAT and IDO levels do not support the theory that activation of IDO/TDO is involved in MDD/BD ( Maes, 2015 ). While the TRYCAT pathway is activated during severe IRS responses, such as acute COVID-19 infection ( Almulla et al, 2022b ) and IFN-α therapy ( Bonaccorso et al, 2002 ), no such changes may be observed in conditions of mild chronic inflammation, such as MDD/BD (this study) and Alzheimer's disease ( Almulla et al, 2022a ). Since plasma/serum TRP concentrations are around 50 μmol/L while KYN concentrations are around 3 μmol/L, TRP is abundantly available as a substrate for KYN formation.…”
Section: Discussionmentioning
confidence: 88%
“…Quality paper controls consists of two scoring scales, namely the quality and redpoints scales, which are detailed in ESF, Table 2 . These rating scales were largely used ( Almulla et al, 2022a , 2022b , 2022c ) to evaluate the methodological quality of the publications that assessed the levels of TRYCATs in individuals with affective disorders. The score on the quality scale varied from 0 to 10, representing lower to better quality, and it focused largely on sample size, control of confounders, and sampling duration.…”
Section: Methodsmentioning
confidence: 99%